Changes of tuning but not dynamics of contrast adaptation with age. (October 2021) - Gao, Yi; Webster, Michael A.; Jiang, Fang
Abstract: Normal aging results in pronounced optical and neural changes in the visual system. Processes of adaptation are thought to help compensate for many of these changes in order to maintain perceptual constancy, but it is uncertain how stable adaptation itself remains with aging. We compared the dynamics of adaptation in young (aged 19–24 years) and older (aged 66–74) adults. Contrast thresholds for Gabor patterns were tracked during and after 300 s adaptation to vertical and horizontal Gabor patches. The time course of contrast adaptation and asymptotic adaptation magnitude were similar between older and young adults when normalized for their respective baseline thresholds. Older adults showed stronger transfer of adaptation to the orthogonal orientation and there was an asymmetry between the transfer of adaptation between the horizontal and vertical orientations for both groups. These results suggest age-related changes in orientation tuning while the processes of cortical contrast adaptation remain largely intact with aging.